DAMPAK SIARAN TELEVISI TERHADAP KEUTUHAN RUMAH TANGGA PASANGAN USIA MUDA DI ACEH - Hamdani. AG (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2021)
This studi, entitle of “The Effect of Television Broadcasting on Household Integrity of Young Couples in Aceh, (Analysis of Three Cases of Violence against Husbands in North Aceh), raises two problem formulations; How is the influence of television broadcasting on household integrity of young couples in Aceh and how the content of television broadcasts affects the violence of wives against husbands and the research objectives are to answer the two problem formulations above. This research is designed as a qualitative research with informants as sources who are selected from various groups including the wife of the perpetrator of the violence themselves. Using the cultivation theory of cultivation theory and the theory of cultural colonization (cultural imperialism theory) as a research guide and scalpel of the existing problems. The research results show that; 1) the influence of the mass media on the integrity of the households of young couples in Aceh through a) cognitive (changes in knowledge) both negative and positive, b) affective (changes in attitudes) and c) behavioral (changes in behavior), these three influences occur due to imitation what they see on the screen, in the form of news, soap operas, films, quizzes and infotainments (coverage of celebrity life) and the violence itself. This change in knowledge, attitudes and behavior encourages women (wives) in Aceh to try to practice it, including the strategy of having an affair with other men, even the strategy of getting rid of (killing) their own legitimate husband. This violence was preceded by domestic conflict (husband-wife squabbling) which continued into two options, first filing for divorce and secondly killing her own husband, especially women with low education and minimal religious teachings (Islam), driven by the pleasure of adultery and male seduction. other. 2) Television broadcast content that affects violence against husbands, especially entertainment broadcast content such as soap operas, films and infotainments that are dry with education, morality and religion. Thus, what is seen in soap operas, films, infotainments and violence itself tends to be imitated and used as a case study by female viewers in Aceh for their practice.